Radiologic Predictors of Surgery in Newly Diagnosed Pediatric Crohn Disease Patients. Issue 6 (December 2016) - Parker, Damien; Karmazyn, Boaz; Steiner, Steven J.
ABSTRACT: Objectives: The aim of the present study was to assess whether small bowel imaging conducted at the time of diagnosis could be used as a predictor of small bowel surgical intervention in a population of pediatric patients with Crohn disease (CD). Methods: A retrospective analysis of small bowel imaging within 30 days of diagnosis of pediatric CD was conducted. Patients were divided into 2 groups based on small bowel imaging: those with no or minor abnormalities (71%) and those with more extensive or obstructive abnormalities (29%). Medical records were reviewed for small bowel surgical intervention and clinic follow-up visits. Results: A total of 232 patients were included in the study group (average age at diagnosis 11.7 years). Twenty-seven patients (12%) underwent small bowel surgical intervention. The relative risk for small bowel surgical intervention was 2.91 in the group with more extensive imaging abnormalities. The majority of increased surgical risk occurred in the first year after diagnosis, when the normal-minor group had a 2% surgical risk and the more abnormal group had a 17% surgical risk. Both groups had a 2% to 3% surgical risk per year after the first year. Conclusions: Small bowel imaging at the time of diagnosis in pediatric CD can help predict the risk of small bowel surgical intervention and should be recommended for all newly diagnosed patients. Nearly one third of our cohort underwent small bowel surgical intervention through 8 years of follow-up. Surgical complications of CD often occur in the small bowel, and counseling families about surgical risk is an integral part of pediatric CD management.